Superior Mesenteric Artery Syndrome: A Case Report of Two Surgical Options, Duodenal Derotation and Duodenojejunostomy - Yagan Pillay (Case Reports in Vascular Medicine, 2016)
Superior mesenteric artery (SMA) syndrome is a rare cause of duodenal obstruction and its management is usually conservative with nasojejunal feeding. The pathophysiology entails the loss of the fat pad between the superior mesenteric artery and the abdominal aorta. This reduces the angle between the two vessels to less than 20 degrees with the resultant compression of the third part of the duodenum. The surgical management is usually a laparoscopic duodenojejunostomy. The two cases in our series had two different surgical procedures with good outcomes in both patients. The surgical management of each patient should be determined on its own merits irrespective of the standard of care.